Hubungan Tingkat Risiko Ergonomi Dan Masa Kerja Dengan Keluhan Muskuloskeletal Pada Pekerja Pemecah Batu - Wahid Thoyib Rivai; - Ekawati; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Musculoskeletal disorders is the complaint that felt in some parts of muscles, start from the lightest complaint to very hurt. Factors that can caused complaints in musculoskeletal system such as awkward working posture, repeated movements, and working period that too long. The aim of this study is to analyze the relation of the level of risk ergonomics and working period with musculoskeletal disorder on stone crusher workers. This research was using observational research with cross sectional design. Population in this research is 30 respondents from 3 stone crusher’s depot. The sample of this research is 30 respondents which was taken by total sampling method. The result of this research showed that respondents that do work with the level of risk ergonomics low risk level (53,3%) and working period ≥ 5 years (70%). Data analysis was using Chi-Square test. The analysis showed (pvalue = 0.073) which means that there was no relation between level of risk ergonomics with musculoskeletal disorders and working period with (pvalue = 0.049) which means that there was relation with musculoskeletal disorders. The suggestion for the workers is to do stretching during 5-10 minute on breaktime to stretch the stiff muscles and body can do recovery